Inside Track to Critical Thinking and Analysis - Mary Deane; Erik Borg (Great Britain Pearson, 2011)
This book is designed for students to use independently to enhance their critical thinking skills. It contains advice and examples of students' writing to illustrate poor performance and demonstrate how to produce effective critical discourse. As university study requires students to demonstrate critical insight, this book shows how to develop this skill by breaking down the thinking and writing processes into steps. It also points out that critical thinking is valued in post-university employment and discusses how to prepare for professional writing.
Keywords: Critical thinking; Analysis